Supervisi Akademik Kepala Sekolah Dalam Mewujudkan Profesionalisme Guru Di SD Negeri Kecamatan Jeumpa Kabupaten Bireuen - Ichwani Ichwani; Iskandar Iskandar; Munawar Munawar (Mathematics Education Study Program, 2025)
The purpose of this study is to analyze the principal's academic supervision in realizing teacher professionalism at Jeumpa District Elementary School, Bireuen Regency. This research approach uses a descriptive qualitative research method. With data collection techniques, namely observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions/verification. The results of the study indicate that the planning of Academic Supervision in this School carried out by the principal is scheduled according to their respective fields of study so that all teachers who teach at the School are supervised by the principal. The principal in carrying out supervision activities uses individual supervision techniques. Individual techniques are the implementation of supervision that is only shown to one teacher, supervision activities do not apply to two or more teachers. The evaluation carried out by the principal with the evaluation can be feedback to the principal on the teacher's performance in delivering learning to students, therefore the success of a learning process is largely determined by the teacher.